Monitoring the Future: A Continuing Study of American Youth (12th-Grade Survey), 2021 - Miech, Richard A. ([Verlag nicht ermittelbar], 2022)
This survey of 12th-grade students is part of a series that explores changes in important values, behaviors, and lifestyle orientations of contemporary American youth. Students are randomly assigned to complete one of six questionnaires, each with a different subset of topical questions, but all containing a set of "core" questions on demographics and drug use. There are about 1,400 variables across the questionnaires. Drugs covered by this survey include tobacco, smokeless tobacco, alcohol, marijuana, hashish, prescription medications, over-the-counter medications, LSD, hallucinogens, amphetamines (stimulants), Ritalin (methylphenidate), Quaaludes (methaqualone), barbiturates (tranquilizers), cocaine, crack cocaine, GHB (gamma hydroxy butyrate), ecstasy, methamphetamine, and heroin. Other topics include attitudes toward religion, changing roles for women, educational aspirations, self-esteem, exposure to drug education, and violence and crime (both in and out of school). Highlights for 2021: Data collection resumed in 2021, with a change to all web-based surveys. Students completed the surveys on their personal or school-provided device. Non-survey variables have been changed or added to facilitate analyses. For details, please see the codebook section "MTF Variable Information - Non-survey variables included in the data files - Survey mode and design variables for 2021" Information about "screen break" issues, where series of questions were originally presented differently in the web-based survey as compared to the 2019/2020 tablet surveys. Please see the codebook and Appendix D for details. For 12th grade: two additional changes to the survey presentation. Please see the codebook section "MTF Variable Information - Non-survey variables included in the data files", and respective appendices for details. Introduction of randomized blocks of questions presented to students. Please see Appendix E. Test of presentation of items in the substance use consequences section on form 3. Please see Appendix F. Additional information is documented in the MTFQchanges2021byForm.pdf and MTFQchanges2021byType.pdf files available for download.